Character Analysis of Perintis Lakeside Public Open Space Bone Bolango Regency With Placemaking Approach - Ratna, Ratna Dwi Ma'sum; Fendy Faizal Gobel; Yohanes P Erick; Mifidyah Putri Palilati (Institute of Educational, Research, and Community Service, 2023)
This study aims to analyze the characteristics of public open space on the edge of Lake Perintis Bone Bolango with placemaking approach. The research method uses a descriptive qualitative approach through observation, documentation and data analysis. The results showed that the character of public open space on the shores of Lake Perintis based on the elements forming the waterfront and data integration in the form of an open park that has a connecting path in the form of a pedestrian area, with the main purpose of arrangement for recreational activities, has a local economic character. Evaluation of the application of the lakeside Perintis public open space placemaking approach has met seven of the eight basic principles of the placemaking approach, namely the principles of community participation, local identity, comfort and safety, flexibility of use, involvement and artistic creativity, environmental sustainability, and long-term planning. The recommendation for the development of public open space on the shores of Lake perintis in the future is to fulfill one of the principles that has not been achieved, namely universal accessibility or access for all.